2015
DOI: 10.1080/08873631.2015.1021093
|View full text |Cite
|
Sign up to set email alerts
|

Religious themes in Central European postage stamps, 2006–2010

Abstract: The countries of Central Europe present a suitable arena for studying the interplay of religion and nationalism. This study explores religious expressions of national identity through the issue of postage stamps, from 2006 to 2010, in seven Central European countries. While the national societies in question exhibit very different religious inclinations, as expressed through a variety of recent, comparable data, quantitative and qualitative analyses of the stamps they issued over a 5-year period enrich our und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Slovak children appear more inclined to declare the importance of religious sites in their own community than those in Poland or Czechia, while the Czech children appear quite secular in comparison. These findings are in line with other recent studies of territorial identities in this area, in which Slovakia showed the highest level of religious identity followed by Poland and then by Czechia (Reeves 2015).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Slovak children appear more inclined to declare the importance of religious sites in their own community than those in Poland or Czechia, while the Czech children appear quite secular in comparison. These findings are in line with other recent studies of territorial identities in this area, in which Slovakia showed the highest level of religious identity followed by Poland and then by Czechia (Reeves 2015).…”
Section: Resultssupporting
confidence: 93%
“…Religion has long been an important dimension of Central Europe's cultural traditions. And while its role and overall significance appears to be shifting due to broad societal changes (Wilford 2010), religion continues to serve as a component of local, regional and even national identities (Reeves 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrates values and ideologies that were important to local people at the time that a place was named. Like stamps, toponyms can act as messengers of local, regional and national identities, communicating conscious and sub-conscious messages about local populations (Brunn 2011;Reeves 2015). Changes to established place names can also signal significant cultural shifts.…”
Section: Introductionmentioning
confidence: 99%